POP-BFRs in consumer products: Evolution of the efficacy of XRF screening for legislative compliance over a 5-year interval and future trends - Sharkey, Martin; Drage, Daniel; Harrad, Stuart; Stubbings, William; Rosa, André Henrique [UNESP]; Coggins, Marie; Berresheim, Harald (Elsevier, 2022)
In 2015–16, a study of approximately 500 waste plastic articles showed that portable X-ray fluorescence (XRF) was up to 95 % effective in screening for compliance with low persistent organic pollutant (POP) concentration limits (LPCLs) on brominated flame retardants (BFRs) in waste. The present study conducted in 2019–20 mirrors that conducted five years prior on a similar number and range of articles, testing the hypothesis that increased use of alternative BFRs as replacements for POP-BFRs will reduce the effectiveness of XRF as a tool for monitoring compliance with LPCLs. In comparing the results, the overall screening efficacy for LPCL compliance reduced from ~95 % to ~88 %, due in part to decreased prevalence of POP-BFRs and potentially increased presence of alternative flame retardants, particularly in goods with shorter lifecycles such as electronics. We additionally examined the impacts of a number of modifications to the XRF measurement protocol on its efficacy, including: using elemental Sb as a qualifier in detecting POP-BFRs in hard plastics; reduced XRF analysis time; and the elimination of background interference using a test stand. The rate at which hard plastics from electronic waste may be analysed by XRF can be substantially improved by reducing analysis time to 5 s, with minimal increase in false exceedances of the LPCL. Monitoring Sb does not appear an effective qualifier for the presence of POP-BFRs, as Sb seems to be used with a range of BFRs. Use of the test stand, while reducing interference, appeared to reduce accuracy when screening low density and thin samples. Despite a seeming increased use of alternative BFRs, screening of waste for compliance with LPCLs using rapid and low-cost screening methods such as portable XRF is still necessary as methods such as GC–MS cannot be scaled up to match the quantities of waste requiring screening.
Keywords: Brominated flame retardants (BFRs); Low-POP concentration limits (LPCLs); Persistent organic pollutants (POPs); Soft furnishings; Waste electrical and electronic equipment (WEEE); X-ray fluorescence (XRF)